Pengaruh Endorsement terhadap Sikap Konsumen dan Minat Pembelian Produk Lipstik Pada Online Shop dengan Media Sosial Instagram - Pradewi, Ratih Galuh; Yuliyanti, Tri; Norhabiba, Fitri (representamen, 2019)
New media has made a significant impact on past media because new media or internet media aremore accessible and used as social media today and are used as a tool to promote goods to be soldonline.This type of research is quantitative. This research was conducted using path analysis with theStatistical Package for Social Sciences (SPSS) program Ver. 23.00 Sample data of 100 respondents tofemale students of SMK 1 Buduran Sidoarjo.The sampling technique used purposive sampling, namelyfor female students of SMK 1 Buduran Sidoarjo because of the technique of determining the samplewith certain considerations. The researcher only conducted a study on Buduran 1 Sidoarjo VocationalHigh School students who have active Instagram users and follow lipstick seller accounts onInstagram social media.The results of this study with the independent variables of consumer attitudesand purchase interest significantly influence the dependent variable, namely endorsement. This showsthat between consumer attitudes and purchase interest is influenced by endorsement.Keywords: endorsement, consumer attitudes, purchase interest, Instagram social media.